O juiz das garantias no processo penal brasileiro como elemento essencial ao sistema acusatório - Silva, Geine Criscia Santos da (2023)
The Brazilian criminal prosecution, duty/power to punish whose holder is the State, has as its guiding source the Code of Criminal Procedure, a legal diploma that dates back to the year 1941, a time when the country experienced the dictatorship of the Estado Novo (1937-1945). As a mark of this historical period, the original wording of the rule has a police-like tone, which dialogues with the inquisitive system, that is, when there is not sufficient separation between the functions of accusing and judging, which does not match, therefore, with the Brazilian scenario inaugurated with the promulgation of the Federal Constitution of 1988. The Brazilian Constitution favors the accusatorial system, in that it leaves the Public Prosecutor's Office with the accusatory function in crimes of unconditioned public criminal action, and criminal prosecution must conform to this system. The wording of the Code of Criminal Procedure has undergone some changes in its text, one of the most significant being the changes arising from the so-called Anticrime Package (Law nº 13,964 of December 24, 2019), which brought, among other innovations, the provision that criminal proceedings must present an accusatorial structure and the creation of the Judge of Guarantees, a magistrate acting in the pre-procedural phase, already existing in other countries. This monograph approaches the figure of the Judge of Guarantees, highlighting the changes caused from its implementation, which for now is suspended due to an injunction by Minister Luiz Fux, of the Federal Supreme Court (STF) and has as main objective to highlight the reasons why the implementation of the Judge of Guarantees is essential for the effectiveness of the accusatorial system. To this end, the main sources used were the Code of Criminal Procedure and the 1988 Federal Constitution, as well as doctrinal and jurisprudential analysis. To this end, the methodological approach of the research was explanatory-qualitative, carried out through a literature review.